The sweet-and-sour soup of Michał Kalecki's political economy - Aleksander Sulejewicz (International Journal of Management and Economics, 2020)
Leszek Jasiński [2019] attempts, as the title indicates, "a reading after half a century" of Michał Kalecki's thought. We dispute the main claim in the book, i.e. that Kalecki has a firm place in contemporary mainstream economics and was the originator of many ideas generally accepted today. On careful reading, virtually none of the models and theories by Kalecki selected by Jasiński for appraisal has entered mainstream neoclassical economic research and graduate academic teaching. Most of his policy advice was also neglected by the Capitalist State, (post)Stalinist "socialist" State, and "Intermediate Regimes" in developing countries. His opus remains original, advanced, insightful but heterodox in all contexts. Our main thesis is that, toutes proportions gardées, Jasiński is signalling an attempt to repeat the absorption of "bastardised" Keynesianism into the mainstream "grand neoclassical synthesis" in the 1940s/50s with selected, reinterpreted, "bastardised" Kaleckian ideas today. We also doubt that the unilinear view of the history of economic thought can be sustained.
Keywords: B22; B29; B31; B59; 650; Michał Kalecki; heterodox economics; economic models; history of economic thought